2023
DOI: 10.3389/fnut.2023.1110536
|View full text |Cite
|
Sign up to set email alerts
|

Gut microbiota modulation in patients with non-alcoholic fatty liver disease: Effects of current treatments and future strategies

Abstract: Non-alcoholic fatty liver disease (NAFLD) is frequently associated with metabolic disorders, being highly prevalent in obese and diabetic patients. Many concomitant factors that promote systemic and liver inflammation are involved in NAFLD pathogenesis, with a growing body of evidence highlighting the key role of the gut microbiota. Indeed, the gut-liver axis has a strong impact in the promotion of NAFLD and in the progression of the wide spectrum of its manifestations, claiming efforts to find effective strat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(21 citation statements)
references
References 149 publications
(161 reference statements)
0
21
0
Order By: Relevance
“…In the last few years, increased interest and knowledge regarding the pathophysiology of NAFLD, the role of the microbiome, and NAFLD-associated diseases such as diabetes mellitus have come to light. Multiple factors (environmental, genetic, and comorbidities) have been shown to modify the gut microbiota [ 24 , 25 , 26 ]. Other studies have demonstrated a correlation between a specific microbial signature and the severity of NAFLD and the prediction of NAFLD-related cirrhosis [ 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…In the last few years, increased interest and knowledge regarding the pathophysiology of NAFLD, the role of the microbiome, and NAFLD-associated diseases such as diabetes mellitus have come to light. Multiple factors (environmental, genetic, and comorbidities) have been shown to modify the gut microbiota [ 24 , 25 , 26 ]. Other studies have demonstrated a correlation between a specific microbial signature and the severity of NAFLD and the prediction of NAFLD-related cirrhosis [ 27 , 28 , 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Clinical investigations have included a wide range of novel therapeutic targets and prospective medications for the treatment of obesity and MAFLD; however, the results and efficacy have not yet been validated. [207][208][209][210] Glucagon-like peptide-1 (GLP-1)is an incretin hormone that originates from the gut. Additionally, it reduces caloric intake and stomach emptying while increasing insulin release through beta cells.…”
Section: Anti-obesity Pharmacotherapymentioning
confidence: 99%
“…Nonalcoholic fatty liver disease (NAFLD) is a significant public health concern and is the primary cause of chronic liver disease. NAFLD is a liver manifestation of metabolic syndrome and is prevalent in obese and diabetic patients [ 1 ]. With the rising incidence of obesity and diabetes worldwide, NAFLD is becoming increasingly prevalent.…”
Section: Introductionmentioning
confidence: 99%